Assessment of the prebiotic potential and bioactive components of common edible mushrooms in India and formulation of synbiotic microcapsules. (15th February 2022) - Moumita, Sahoo; Das, Bhaskar
Abstract: Pleurotus spp. are listed among "mushroom nutraceutical" accredited to their nutritional and medicinal attributes. In this present study, five different common edible mushrooms i.e., Pleurotus (P.) ostreatus, Pleurotus (P.) florida, Pleurotus (P.) sajor-caju, Agaricus (A.) bisporus and Lentinus (L.) edodes were screened for the highest prebiotic content. Their beneficial bioactive (eritadenine, flavonoid and polyphenol) and prebiotic (β-glucan and inulin) components were quantified by different biochemical and High Performance Liquid Chromatography (HPLC). The mushroom extracts were then evaluated for their compatibility with the potential probiotic lactic acid bacteria ( Enterococcus (E.) faecium and Lactiplantibacillus plantarum) to formulate synbiotic microcapsules. P. florida extract showed highest β-glucan and very high inulin content so it could act as a great source of prebiotics. Besides, the extract from P. florida contained the highest concentration of eritadenine and was also found to be most compatible with E. faecium, confirmed by its high prebiotic activity score in comparison with the commercial prebiotic i.e., inulin. Furthermore, the probiotics selected for the formulations of the microcapsules have high potential for therapeutic applications, antihypertensive and hypocholestromeic activity. Therefore, the formulated microcapsules as such or when incorporated into food matrices (therapeutic food) might be effective in decreasing blood pressure and blood cholesterol. Graphical abstract: Image 1 Highlights: Eritadenine, flavonoid & polyphenol (bioactive) contents of 5 mushrooms quantified. Prebiotic components (β-glucan and inulin) of the mushrooms were estimated. Potential probiotics & the mushroom extracts were evaluated for best combination. Highest compatibility was seen between P. florida extract & E. faecium (probiotic). Short-chain fatty acids produced upon fermenting P. florida extract by E. faecium.